The Influence of Marketing Strategy Model for Halal Food Brand Equity in the Southern Border Provinces of Thailand - Sungnoi, Pattareya; Ouparamail, Wisanan; Khemthong, Suree; Angsuchoti, Supamas (Hatyai Academic Journal, 2023)
The purposes of this research were 1) to study the consumer behavior components, marketing mix, integrated marketing communication, value added, and Halal food brand equity in the southern border provinces of Thailand, and 2) to analyze marketing strategy models that influence Halal food brand equity in the southern border provinces of Thailand. This research was a quantitative research. The data were collected from 460 Muslim consumers living in the southern border provinces of Thailand and whose age up to 20 years old and above, with a determining sample proportion of gender, age and province. In addition, this research used the stratified random sampling by each province, the data were analyzed by descriptive statistics, confirmatory factor analysis and structural equation modeling analysis. The results indicated that 1) consumer behavior components, marketing mix, integrated marketing communications, value added, and brand equity Halal food related to the empirical data which an index value criterion, and 2) brand equity was direct influence from value added and indirect influence from consumer behavior, marketing mix, and integrated marketing communication influence through added value with statistically significant at the 0.05 level.